EFEKTIVITAS ALUMINIUM SULFAT DAN KAPUR DALAM MENURUNKAN BIOLOGICAL OXIGEN DEMAND (BOD) DAN TOTAL SUSPEND SOLIDS (TSS) PADA LEACHATE - Saudin Yuniarno; Kuswanto Kuswanto (Kesmas Indonesia, 2008)
rubbish or refuse is a part of something that cannot be used, unvorable or something that must be thrown and commonly produced from the activities done by human. The rubbish in the landfill will be docomposed, and it will result leachate. If the leachate is not well managed, it will contaminate teh ground water and surface water in Gunungtugel landfill, Purwokerto. The method of research used was experimental research and the type of the research was explanatory. The research aims to study the effectively of Alluminium Sulphate and Calcium in decreasing Viological Oxygen Deman (BOD) an Total Suspende Solid with quasi experimental research design and the research design used was pre test post test control group design. The statistic test used was paired t tes, anova with meaning level was 95 %. from the pre treatmnet research, the BOD average resulted was 283,30 mg/lt and TSS 325,88 mg/lt, with BOD content after treatment : dosage 4 g/lt=87, 16 mg/lt, dosage 5 gr/lt = 75,37 mg/lt; dosage 6 gr/lt = 91,88; dosage 7 gr/lt = 117,22 mg/lt. Meanwhile the average of TSS content after treatment was; dosage 4 gr/lt = 64,99 mg/lt; dosage 5 gr/lt; dosage6 gr/lt = 73,68 mg/lt; dosage 7 gr/lt = 112,27 mg/lt. The effective dosage resulted was 5 mg/lt. But if it is compared to SK MenKLH No. Kep 03/MenKLH/II/1991, this dosage has justfulfilled the type III of basic quality standard. The researcher suggest that dor the better result, the use of Alluminium Sulphate and Calcium are separated, so the ability of each coagulant in v=bonding organic can be more maximized. The use of Calcium will be more effective if all the flocks of the coagulation process used Alluminium Suffate have settled.